Seasonal optimality of high intensity physical activity for men of mature age - Pryshva, O.B. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2018)
Aim. To study and compare the seasonal response of men’s cardiovascular system to physical activity of high intensity with average annual rates. Determine the optimal seasons for the intensification of occupations by physical activity of high intensity. Material. The study was attended by men aged 40-55 years old (n=18), leading a healthy lifestyle. All men do not have chronic illnesses. All men have the experience of independent occupations of high intensity physical activity. Men live in the south of Ukraine. For 12 months, daily (after a night sleep) the body weight, heart rate, and arterial pressure were recorded. Calculated: body mass index, cardiovascular system tension. Physical activity was measured by bioresigners Basis B1, Peak. Results. In winter, the overall physical activity of men was significantly lower (by 11.37%) than the average annual. Physical activity of high intensity was lower by 21.61%. In summer, the time of men’s employment has significantly decreased (by 4.11%) for the average annual. In autumn period, the total physical activity was significantly higher (4.73%) than the average annual. Conclusions. It was determined that the physical activity of high intensity during all seasons positively affects the physical condition of men. It reduces the tension of the cardiovascular system. It is advisable to predict the summer season as the most optimal for the intensification of the physical activity of high intensity of mature age men.